Correlation between Students' Mathematical and Logical Spatial Intelligence in Terms of Understanding Concepts - Zaiyar, M; Rusmar, Irfan; Yuniarti, Trisna (Malikussaleh Journal of Mathematics Learning (MJML), 2020)
This study aims to determine the relationship of junior high school students’ spatial and mathematical logical intelligence based on understanding the concepts. Spatial intelligence indicators in this study are reviewed from students’ abilities in using images as a tool for solving problems, connecting data with concepts that have been held, and finding patterns in solving problems. On the other hand, the indicators of students’ mathematical logical intelligence is observed by looking at students' abilities to mention and understand information that is known in a problem, to draw up a plan of completion and to do mathematical calculations correctly. The indicators of understanding concepts are restating a concept, providing examples and non-examples of concepts, and applying concepts or algorithms in problem solving. The research method in this research is the Ex Post Facto correlational type, with using a purposive sampling as the sampling technique. The results of the data analysis obtained a correlation coefficient is around 0.93 with 86% R square. The relationship between the spatial intelligence variables is shown by the understanding of concepts by 86%, the level of the relationship, with the correlation coefficient is 0.93, where mathematical logical intelligence with an understanding of 80%, with the level of the relationship of 0.89, and the relationship of spatial intelligence with a mathematical logical is described by a 77% level of the relationship, with 0.88, as the correlation coefficient. The results showed that there was a very strong relationship between spatial intelligence and logical mathematics in terms of understanding students' concepts.